Optimization of ultrasound assisted extraction of the Sea buckthorn leaves, characterization of the phenolic compounds, and determination of bioactive properties of the extracts - Nora Pap; Pertti Marnila; Juha-Matti Pihlava; Jenni Tienaho (Future Foods)
Sea buckthorn leaves are known to be rich in antioxidants and phenolic compounds. However, non-proper processing methods can result in a decrease of the beneficial properties. To address this, response surface methodology (RSM) was used in the modelling and optimizing of the ultrasound assisted extraction of the sea buckthorn leaves to obtain high yields of total phenolics content in the extract. The alike obtained extracts were subjected under investigations of bioactivities such as the antioxidant activities (FRAP and ORAC), antibacterial properties against Staphylococcus aureus and Escherichia coli and anti-inflammatory characteristics. The results indicated that the extracts obtained under the optimal process conditions of 30 min, continuous pulse, and solid to liquid ratio of 0.2 showed antioxidant activity, and antibacterial activity against both Gram+ and Gram– bacteria at a moderate level. The extracts are rich in polyphenolic compounds, such as ellagic acid and flavonoids. The in vitro anti-inflammatory tests with THP-1 promonocyte model indicated that the sea buckthorn leaf extract obtained by ultrasound assisted extraction has powerful anti-inflammatory properties. These results prove that the ultrasound assisted extraction of sea buckthorn leaves provides a good source of phenolic compounds that have versatile bioactive properties and can generally be regarded as health promoting food compounds.